PEMANFAATAN BIOENZIM DARI LIMBAH BUAH MANGGA (Mangifera indica)TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Mentari, Yoan Aprilia; Kurniawan, Andri; Robin (Program Studi Akuakultur, Universitas Bangka Belitung, 2026)
The agricultural and plantation industries in Bangka Belitung produce large amounts of organic waste, including mango (Mangifera indica) waste, much of which is not optimally utilized. One alternative utilization is through the production of bioenzymes that can be applied in aquaculture systems. This study aims to analyze the effect of bioenzymes from mango waste on the growth, survival rate, and water quality of tilapia (Oreochromis niloticus) fry. The study was conducted experimentally using four treatments: one control pond without bioenzymes and three experimental ponds with different bioenzyme doses. Parameters observed included length growth, weight gain, survival rate, and water quality during the rearing period. The use of bioenzymes from mango waste has been shown to have a positive impact on tilapia seed cultivation. The administration of bioenzymes, particularly at a dose of 40 ml, was able to optimally enhance the growth of fish fry, as evidenced by increases in weight, length, and specific growth rate. Furthermore, fish survival rates across all treatments remained in the good category, indicating that the use of bioenzymes did not negatively impact the survival of fish fry. Aquarium water quality also remained stable within the optimal range throughout the study, with the 40 ml dose showing the best performance in maintaining parameters such as DO, pH, temperature, EC, and TDS. This water quality stability indicates that bioenzymes play a role in accelerating the decomposition process of organic matter, thus creating a more supportive environment for fish growth. Overall, bioenzymes from mango waste have great potential as an environmentally friendly technology that can increase the productivity of tilapia cultivation by improving growth, survival, and water quality.